(untitled) (Analysis in Theory and Applications, 2023)
In this paper, we establish global C^2 estimates to the Neumann problem for a class of fully nonlinear elliptic equations. As an application, we prove the existence and uniqueness of k-admissible solutions to the Neumann problems.